Automated Calibration Robotic System Capable of Producing Versatile Force Combinations for Multiaxis Force/Torque Sensors - Hwang, Jinhak; Lee, Woosung; Lee, Seran; Kim, Yong Bum; Kim, Uikyum (IEEE Transactions on Industrial Informatics, 2024)
In this study, we describe the development of a novel calibration robotic system, which is capable of automatically generating various combinations of a six-axis force/torque (F/T) that measures the maximum force information at a point. We proposed a new principle for generating a six-axis F/T by using three vertical forces and three horizontal forces based on a kinematic model. The mechanism of the proposed system was designed and manufactured compactly using a pulley-driven mechanism and a wire-driven mechanism. Consequently, versatile combinations of the F/T were generated by using the force/position control of six motors in the system, and their performance was validated by comparing the data with that of a commercial six-axis F/T sensor. Results showed an error of less than 1.6%. In addition, performance validation was further conducted using artificial intelligence techniques to obtain accurate data with an error below 0.025%.
Keywords: Automated calibration; Automated calibration system; Calibration system; Force; Force calibration; Multi-Axis; Multiaxis force calibration; Robot sensing system; Sensor systems; Six-axis force/torque sensor; Versatile force combination; Automated calibration system; multiaxis force calibration; six-axis force/torque (F/T) sensor; versatile force combination